Does corporate governance spillover firm performance? A study of valuation of MENA companies - Arayssi, Mahmoud (2019)
Purpose The aim of the paper is to examine the association of corporate governance (CG), the firms’ characteristics and the financial performance of firms operating in the Middle East and North Africa (MENA) region after Arab Spring. The study focuses on CG, exemplified by boards’ composition and ownership structure. It also explores the possible moderating effects of environmental social and governance characteristics (ESG), leverage and size on the relationship between CG and the company’s performance. Design/methodology/approach Using Thomson-Reuters database, a sample of 67 firms was extracted in the MENA region to measure CG and financial performance post Arab Spring from 2012 to 2016. Panel GLS regression random effects is used to quantify the relationship; robustness is checked by using several alternative regressions and specifications to the performance measure. Findings The results reveal that board independence (BI) is negatively correlated with firm profitability but ownership concentration and board gender diversification contribute to profits. When firms that voluntarily form a governance committee are examined, ownership is less concentrated. We obtain a stronger impact of good governance on performance in these firms: board composition, in general, and workers’ satisfaction generate more profits; and undertaking ESG activities become a more dispensable activity. The effect of board size (BS) and forming a governance committee are studied and ensuing recommendations are drawn. In addition, relevant internal control of firms’ characteristics that strongly predict firms’ market values are discussed in the context of agency and stewardship theories. Originality/value Despite the fact that governance-performance nexus has been extensively discussed and examined, the focus of this volume of research is on western developed countries. The growing economies of the MENA countries, and the limited governance-performance literature in the MENA context have created a demand to understand the governance environment in these countries and its influence on firm’s performance. In this region where firms’ owners are mainly family members, governments and/or institutions, governance is typically weak; moreover, ownership concentration is expected to guarantee good performance, as the role of independent directors becomes ineffective. For firms where ownership is more diluted, a sound governance system should be established to replace ownership concentration, and to more efficiently monitor management, and consequently improve firm performance. Therefore, this study not only contributes a summary of the prevailing corporate structure in MENA. Moreover, it explains the settings where both the stewardship and agency theories apply in MENA firms. Some recommendation on the importance of changes to the existing governance rules are highlighted in terms of more rules requiring board independence, board gender diversity, limits on board size and establishing governance committees.